The CesÃ ro Operator on Some Sequence Spaces in Riesz Space of Non-Absolute Type - E. Herawati; Supama (Journal of Research in Mathematics Trends and Technology, 2020)
The CesÃ ro operators are investigated on the class -valued sequence spaces , and with is a Riesz space. Besides, we also carry out that are order bounded operators.